Effects of normative beliefs about stopping cyberbullying on bystander helping behavior - Chia-Lin Chang; Cheng-Hong Liu; Xian-Rui Yin; Kuan-Ming Chen; Ting-Huan Lin (Computers in Human Behavior Reports)
Cyberbullying research has yet to explore how bystanders' normative beliefs about stopping cyberbullying (NBSCs) influence their actions. We examined the effects of NBSCs on bystanders’ helping behaviors and the underlying mechanisms. In Study 1, 195 undergraduate participants completed a measure of NBSCs and reviewed a scenario describing a student experiencing cyberbullying. Results showed that individuals with higher NBSCs demonstrated greater helping behavior. This relationship was sequentially mediated by perceived urgency of the situation, state empathy, and a sense of responsibility to help. In Study 2, 82 participants were assigned to either a control group or an experimental group designed to enhance NBSCs. The NBSC group exhibited more helping behaviors, with mediation patterns similar to Study 1. These findings highlight the critical role of NBSCs in fostering bystander intervention and suggest that anti-bullying organizations, educators, and online platforms should implement strategies to promote NBSCs in efforts to combat cyberbullying.